Avaliação dos impactos às competências dos profissionais contábeis após o projeto SPED - Aguiar, Gisleise Nogueira de (2012)
The global market has invited professionals from diverse fields to evolve similarly to the speed of technology and the new economy. These changes will certainly result in paradigm shifts, changes in skills and image in organizations, for accounting professionals. As buster for the new scenario, the Brazilian government has developed the Digital Bookkeeping Public System (SPED), whose main goal is to replace the accounting and fiscal procedures of the companies for digital controls in order to improve the management of the levy. In this context, the professional accounting should redirect its activities relying on what is most advanced in technology and act as an integrator of information. This study aimed to assess the impacts to obtain the skills of accounting after the project realization by SPED specialists. The methodology we used field survey, conducted with 17 project leaders SPED, and all accounting professionals. The survey shows that there is still a waste of time these professionals with the generation of tax and accounting reports, however there are expectations of reduction of the time with the evolution of the project SPED, and as well as providing greater availability of professional study and development of new skills. In addition, the research highlights possible changes to the image of the professional performing its actual function in the digital world, which is contributing to improving society as a whole